Traditional Investigation of Bacterial Pathogens in Urine of Adult Cows - Hala S.R. AL-Taee; Mohammed H.M. Merah; Baidaa H.R. Al-Mahna; Hasanain A.J. Gharban (The Bioscan, 2025)
Bacterial infections can have severe effects on the body systems of animals and humans, and reducing the growth rate and increasing the morbidity and mortality of cattle. Urinary tract infection (UTI) is one of the health problems that cows suffering from it in most countries, and consider as the second most common disease after respiratory tract infection. This study aims to identifying the pathogenic bacteria implicated in occurrence of UTIs in cattle of Wasit province (Iraq). Totally, 135 urine samples were collected from female cattle including 86 samples from those does not calving previously and 49 urine samples from cows calving for one time. The results showed there were 81.4% of positive isolates distributed among 39 first calving, and 71 non-calving cows. The percentage of types of bacterial infection were 31.8%, 18.2%, 14.5%, 12.7%, 12.7%, and 10% for Escherichia coli, Proteus mirabilis, Klebsiella pneumonia, Pseudomonas aeruginosa, Staphylococcus epidermidis, and Staphylococcus aureus, respectively. In conclusion, this variety of bacterial infections is important in treatment process, preserving the animal, reducing the risk of reproductive infections, and controlling UTIs in cows, especially before and after calving.